Remote triage and the oncology patient experience. Issue 28 (1st October 2022) - Hoegger, Blake; Townsend, Sydney; Ortega, Lance; Mikan, Sabrina Q.; Patt, Debra A.; Books, Holly
Abstract : 297 Background: Investments in infrastructure to enhance care delivery are often partnered with practice participation in alternative payment model contracts and innovative care delivery models. Oncology nurses routinely are physically located in a cancer practice. We sought to understand the impact of centralizing resources to work remotely building upon triage pathways already in place on staffing and symptom call resolution with the goal of optimizing outpatient symptom management and patient satisfaction. Due to a national RN shortage and a historical high number of RN vacancies in oncology, we thought this this innovative staffing solution may attract, retain, and elevate the role of RNs. Methods: A needs assessment was conducted to evaluate call volumes, staff levels and duties. A gap analysis was performed to determine which duties would be assigned to remote triage versus in person staffing. Some sites had triage; all sites upgraded to new optimization of assessment and management. Standardized evidence based care and communication pathways were implemented. RNs were trained to follow structured workflows for call ticket resolution. A regional pool supported primary triage RNs who were assigned to each site. The model allowed for flexible staffing while building and maintaining relationships with local providers. Additionally, remote triage RNs were given the opportunity to augment their assessment with audio/visual telehealth as needed. Results: In the first 4 months, 9 pilot sites decreased symptom management time by 50%; 1 site decreased by 70% (over 120 minutes down to 27 minutes). Since remote triage began, average resolution times reduced from 2.52 hours to 1.31 hours. One pilot site had an in-person triage position posted and attracted 4 applicants over 4 weeks. When the position was converted to a remote role, 38 applications were received in 1 week. Offering remote triage positions allowed RN recruitment from other states and gave tenured RNs within the organization an attractive new work model. Conclusions: Remote RN work is an attractive opportunity for RNs allowing for broader recruitment of candidates. Removing triage RNs from the clinic site allows them to focus on triage resolution and as a result call resolution times decreased substantially. Standardized communication pathways were developed, rolled out, and optimized in both virtual and in-person Triage RN roles statewide. Adherence to these communication pathways is critical to ensuring timely symptom management resolution and a sustainable workforce.